2017
DOI: 10.3389/fphys.2017.00180
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Critical Power and W′ in Hypoxia: Application to Work-Balance Modelling

Abstract: Purpose: Develop a prediction equation for critical power (CP) and work above CP (W′) in hypoxia for use in the work-balance (WBAL′) model.Methods: Nine trained male cyclists completed cycling time trials (TT; 12, 7, and 3 min) to determine CP and W′ at five altitudes (250, 1,250, 2,250, 3,250, and 4,250 m). Least squares regression was used to predict CP and W′ at altitude. A high-intensity intermittent test (HIIT) was performed at 250 and 2,250 m. Actual and predicted CP and W′ were used to compute W′ during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 47 publications
2
29
1
Order By: Relevance
“…The opposing responses of CP and W′ in this experiment may have been artifactually caused by the hyperbolic form of the model (see section below on “Model Bias and Artifacts”). In contrast, acute hypoxia treatment to simulate various altitudes decreases CP ( Parker Simpson et al, 2014 ; Townsend et al, 2017 ) in a dose-response manner consistent with observed decrements in O 2max ( Townsend et al, 2017 ). Specifically, CP decreased in proportion to simulated altitude, with significant reduction evident at 1,250 m. W′ was less sensitive to altitude change than CP as it was significantly reduced only at a simulated altitude of 4,250 m.…”
Section: Evaluation Of the Cp Model For Doping Detection: Promise Andsupporting
confidence: 79%
See 2 more Smart Citations
“…The opposing responses of CP and W′ in this experiment may have been artifactually caused by the hyperbolic form of the model (see section below on “Model Bias and Artifacts”). In contrast, acute hypoxia treatment to simulate various altitudes decreases CP ( Parker Simpson et al, 2014 ; Townsend et al, 2017 ) in a dose-response manner consistent with observed decrements in O 2max ( Townsend et al, 2017 ). Specifically, CP decreased in proportion to simulated altitude, with significant reduction evident at 1,250 m. W′ was less sensitive to altitude change than CP as it was significantly reduced only at a simulated altitude of 4,250 m.…”
Section: Evaluation Of the Cp Model For Doping Detection: Promise Andsupporting
confidence: 79%
“…τ w′ was observed to increase (i.e., recovery took longer) as a function of the recovery intensity. Subsequent studies further revealed the sensitivity of τ w′ to work and recovery bout durations ( Skiba et al, 2014a ) and to environmental conditions ( Townsend et al, 2017 ).…”
Section: Critical Review Of the W′ Bal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…(61,63,79,91)). An alternative approach has been proposed by Hill (51), and recently adopted by some researchers (18,19,101), whereby the model producing the lowest standard error of estimate (SEE) is used. We therefore recommend that the P-T relationship should be characterised with the 2-parameter model that results in the lowest SEE.…”
mentioning
confidence: 99%
“…These effects are observed on mountainous compared with flat stage races, despite the negative influence of altitude on cycling performance. Indeed, environmental conditions such as hypoxia and heat impair power production and their effects would need to be considered when comparing cycling performances (Nybo, 2010 ; Garvican-Lewis et al, 2015 ; Townsend et al, 2017 ). While research has attempted to predict the effects of acute hypoxia on exercise capacity (i.e., critical power), the effects of environmental heat on performance is not immediate and complicated by many factors including convective cooling, blood distribution, core, skin, and environmental temperature gradients.…”
Section: Field Data and Performance Modelingmentioning
confidence: 99%